Geopolitical risk shocks: When the size matters - Davide Brignone; Luca Gambetti; Martino Ricci (European Central Bank (ECB), 2024)
In this paper, we investigate the presence of non-linearities in the transmission of geopolitical risk (GPR) shocks. Our methodology involves incorporating a non-linear function of the identified shock into a VARX model and examining its impulse response functions and historical decomposition. We find that the primary transmission channel of such shocks is associated with heightened uncertainty, which significantly escalates only with substantially large GPR shocks (i.e., above 4 standard deviations). This increase in uncertainty prompts precautionary saving behaviors, exerting a strong impact on consumption and reducing activity. The response of inflation is more subdued, reflecting both diminished demand and heightened uncertainty, which influence prices in opposing directions.
Keywords: C30; D80; E32 F44; H56; 330; Geopolitical Risk; Economic Activity; Inflation; Vector Autoregressions; Uncertainty